Diagnósticos, resultados e intervenções de enfermagem para pessoas idosas em situação de violência - Brandão, Bárbara Maria Lopes da Silva (2023)
Introduction: The use of nursing terminologies, such as the International Classification for Nursing Practice (ICNP® ), helps in the organization and systematization of care, given the standardization of vocabulary and consolidation of care standards. In the context of elder abuse, it is necessary to structure diagnoses/outcomes and nursing interventions that organize and facilitate the language of nursing in the execution of integrated care to senescence needs and violence. For this construction, the Theory of Forensic Nursing Care was chosen as a theoretical support to support the structuring and expand the possibilities of care. Objective: To elaborate statements of diagnoses, outcomes and nursing interventions for older adults in situations of violence, based on the Theory of Forensic Nursing Care. Method: This is a methodological study, developed according to the criteria for the elaboration of terminological subsets, arranged by the stages of identification of terms relevant to the clientele and/or health priority, extracted using PorOnto tool; cross-mapping of terms identified with ICNP® 2019/2020 terms; and construction of statements of diagnoses, outcomes and nursing interventions. It was submitted to the Research Ethics Committee and approved under Opinion 3,709,600/2019. Results: In the first stage, 10,731 terms were extracted from 19 articles obtained in the scoping review. After the normalization and standardization process, 1,236 terms were submitted to validity, resulting in 704 terms. Then, with cross-mapping, 293 constant terms and 411 non-constant terms were identified in ICNP® , version 2019/2020. In the last stage, 97 statements of nursing diagnoses/outcomes, and 219 of nursing interventions, were prepared, which were classified according to the Theory of Forensic Nursing Care statements. Conclusion: The present study achieved its objectives with the construction of statements of diagnoses, outcomes and nursing interventions, which may enable the clinical reasoning of the nursing process, aligned with forensic nursing skills, to support autonomous and effective assistance to the target audience. Subsequent studies are recommended to carry out the statements’ content and clinical validity and to structure a terminological subset with unified language.